Imobilização e detecção de biomoléculas em matrizes de poli (ácido 4-hidroxifenilacético) : aplicações no desenvolvimento de genossensores - Silva, Tatiana Aparecida Rosa da (2008)
Modified electrodes with polymer films are efficient matrix to biomolecules immobilization. Therefore due the anionic or cationic surface functionalization, they promote the electrostatic repulsion of interferents and efficient interaction with immobilized biomolecules. Of this form, they stimulate great advance in the development of biossensors and sensors. Aiming at the incorporation of nucleotides, oligonucleotides and DNA fragments were made studies of the electropolymerization of the 4-hydroxyphenylacetic acid monomer on graphite surface, to obtain the best condition of polymerization and characterization of the surface. In more acid pH values, was observed the films formation with bigger electroactive character and with higher electrons transference in redox K3Fe(CN)6/K4Fe(CN)6. The characterization of these films by means of AFM and SEM confirmed the deposition of the polymer onto surface. Electrooxidation and optimization studies of the adenosine monophosphate and guanosine monophosphate immobilizated onto poly(4-HPA) films were carried out at different pH values. Variation of the experimental conditions, particularly of the pH of the electrolytic solution, showed that the oxidation potentials of immobilized AMP or GMP onto the modified electrodes decreased with increasing of pH values of the solution. Higher oxidation current was obtained to AMP in phosphate buffer (pH 7.50) and GMP in acetate buffer (pH 4.50). The immobilization and detection of oligonucleotide of 16-pb were carried out on the poly(4-HPA). In the detection process with the complementary target was observed decrease in the values of current, when compared with the response obtained before of the hybridization. The magnitude of the current signal of the eletrooxidation of nucleotides or oligonucleotides was bigger for the modified graphite electrodes with poly(4-HPA), in relation to the graphite electrodes without modification. The amplitude of the current signal is an important parameter that guarantees the sensitivity of the biosensors. The immobilization and detection of DNA fragments of the dengue virus (DEN- 1) was carried out using ethidium bromide as hybridization indicator. The dsDNA formation was monitored by means of the increase in the current signal, caused by accumulation of the intercalator on the surface of the electrode. Images of the surface topography for AFM indicate that the DEN-1 (ssDNA) immobilization on the polymeric matrix results in reduction of the roughness and, after the hybridization with the complementary target (dsDNA), was observed formation of higher globules number. The AFM images showed the immobilization of biomolecules in study and suggest the hybridization with the complementary target.